Coupled Rigid-Block Analysis: Stability-Aware Design of Complex Discrete-Element Assemblies. (May 2022) - Kao, Gene Ting-Chun; Iannuzzo, Antonino; Thomaszewski, Bernhard; Coros, Stelian; Van Mele, Tom; Block, Philippe
Abstract: The rigid-block equilibrium (RBE) method uses a penalty formulation to measure structural infeasibility or to guide the design of stable discrete-element assemblies from unstable geometry. However, RBE is a purely force-based formulation, and it incorrectly describes stability when complex interface geometries are involved. To overcome this issue, this paper introduces the coupled rigid-block analysis (CRA) method, a more robust approach building upon RBE's strengths. The CRA method combines equilibrium and kinematics in a penalty formulation in a nonlinear programming problem. An extensive benchmark campaign is used to show how CRA enables accurate modelling of complex three-dimensional discrete-element assemblies formed by rigid blocks. In addition, an interactive stability-aware design process to guide user design towards structurally-sound assemblies is proposed. Finally, the potential of our method for real-world problems are demonstrated by designing complex and scaffolding-free physical models. Highlights: CRA method: 3D analysis and design of complex rigid-block assemblies with friction. Nonlinear constrained optimisation coupling static equilibrium with kinematics. Penalty formulation to measure structural infeasibility and identify unstable regions. Stability-aware design process towards more stable design solutions. Design, fabrication and construction of complex, scaffolding-free assemblies.